Situlung: Social Capital in The Farming Community in Bulutellue Village, Bulupoddo District, Sinjai Regency - Abdul Rahman (PT. Gudang Pustaka Cendekia, 2026)
This study aims to determineBaliin the farming community in Bulutellue Village, Bulupoddo District, Sinjai Regency and To find out the factors that influence situlung in the farming community in Bulutellue Village, Bulupoddo District, Sinjai Regency. In this study, a qualitative research type was used which was analyzed and written descriptively. Data collection techniques were carried out using observation, interview and documentation methods involving 10 (ten) informants. Based on the results of the study, it shows that: (1) situlung in the farming community in Bulutellue Village begins with the awareness of each individual that as social beings they cannot live alone. This situlung activity is divided into several activities, namely starting from hoeing, planting, carrying, building houses, and party events such as weddings, aqiqah and thanksgiving. All of this work is carried out in a situlung manner which contains the values of togetherness and unity. Over time, this situlung has experienced a shift in values caused by social changes that take place continuously without being realized by the surrounding community. In addition to one of the situlung activities that still exist from the past until now, namely mappegau (2) factors that influence situlung in the farming community in Bulutellue Village are inhibiting factors and driving factors. The inhibiting factors for situlung in the rice farming community are modernization and economic demands, both of which have a significant influence on the lives of farming communities, which change society from a society that needs each other to an individual society. Apart from these inhibiting factors, family ties and religion are supporting factors for situlung to remain in a community.